PENGUATAN KARAKTER RELIGIUS ANAK TAMAN PENDIDIKAN AL-QUR’AN AL HUDA CANGGAL MELALUI FILM ANIMASI NUSSA DAN RARA - Yenny Aulia Rachman; Salamah Salamah; Agustina Putri Reistanti (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
The purpose of implementing community service activities is to depict the role of TPQ (Islamic Education Institution) in religious character education and the internalization of religious character education within TPQ. This service activity utilizes Participatory Action Research (PAR), an action research method resulting from planning, taking action, and evaluating the outcomes of those actions. Strengthening the religious character of students at TPQ AL HUDA is achieved through habituation. The activities begin with regular Quranic studies using the Yanbu'a method and the analysis of Islamic texts and supplications. Subsequently, at the end of the Quranic study session, the internalization of religious character strengthening is carried out through the habituation of learning religious character with the visualization of the "Nussa and Rara" film. Following this, the teachers reinforce religious character within TPQ and encourage the students to seek positive advice in their daily activities. This method effectively engages students in Quranic studies and indirectly instills the values portrayed in the film in the children's hearts.